Differential effects of paraquat-induced oxidative stress on functional aging and lifespan in male and female Drosophila melanogaster - Mehmet Fidan (PLoS ONE, 2026)
Aging is accompanied by loss of motor function driven by mitochondrial oxidative stress. To examine how genotype and sex modulate this process, we exposed Oregon-R (wild-type) and vestigial (wing-deficient) Drosophila of both sexes to chronic paraquat a mitochondrial stressor generating sustained ROS production at 0, 10, or 20 mM. We tracked climbing performance from day 5–50 alongside survival. Paraquat impaired locomotion dose- dependently, with effects modified by genotype and sex (four-way ANOVA, all p < 0.001). Under control conditions, behavioral half-life (T₅₀) occurred at 21.4 days in Oregon-R males and 25.7 days in females. Vestigial flies declined earlier: 14.8 days (males), 18.3 days (females). At 20 mM, T₅₀ fell 48–53% across groups. Female advantage persisted at 10 mM but narrowed at 20 mM, especially in vestigial flies. Survival mirrored functional decline. The T₅₀-to-lifespan interval compressed under severe stress: 18–28 days (controls) versus 8–12 days (20 mM). Functional-survival coupling was strong (r = 0.87, p < 0.001). Oxidative stress accelerates functional aging through mechanisms shaped by genotype and sex. Climbing performance predicts healthspan and may serve as a translational biomarker for neuromuscular aging.